Forsterite particles and method for producing forsterite particles
By using technetium compounds as a medium in the production of garnet particles, the problem of insufficient performance of garnet particles in the prior art is solved, and garnet particles with catalytic activity and low aggregation are efficiently prepared.
Patent Information
- Application Number
- JP2024525009
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-04-28
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2042-04-28
AI Technical Summary
In the prior art, there is limited knowledge about conventional garnet particles, and there is room for improvement in the production method, making it difficult to prepare garnet particles with excellent performance.
By using technetium compounds as a medium, garnet particles are prepared to control the content and surface distribution of technetium, and the catalytic activity and shape control ability of the particles are improved.
It realizes efficient production of garnet particles, has excellent catalytic activity and low aggregation, and can control the shape and size of the particles.
Smart Images

Figure 0007663155000003 
Figure 0007663155000004 
Figure 0007663155000005
Abstract
Description
[Technical field]
[0001] The present invention relates to forsterite particles and a method for producing forsterite particles. [Background technology]
[0002] Forsterite has excellent strength and is used as a thin-walled insulating material. It also has high insulation resistance and is widely used as an electrical insulating material. Furthermore, due to its large thermal expansion coefficient, it is used in places where adhesion to metals is important, such as insulating parts for vacuum tubes and base materials for metal film resistors.
[0003] Forsterite also has a dielectric constant of 6.5, a small dielectric tangent (Tan δ) and low microwave loss, making it useful as a high-frequency insulating material. It is an inorganic material that is expected to be used in the future as 5G becomes more widespread.
[0004] Patent Document 1 discloses a method for producing forsterite microparticles, in which a solution containing a water-soluble magnesium salt and colloidal silica in a molar ratio of magnesium atoms to silicon atoms (Mg / Si) of 2 is sprayed into an atmosphere at a temperature of 50°C or higher and lower than 300°C, dried, and then fired in air at a temperature of 800 to 1000°C to obtain forsterite microparticles with a primary particle size in the range of 1 to 200 nm as determined by observation with an electron microscope.
[0005] Patent Document 2 discloses silane-treated forsterite fine particles, and the production method thereof includes: (a) step: 5 to 100 m 2The method for producing an organic solvent dispersion of silane-treated forsterite microparticles includes the steps of: (a) wet-grinding forsterite microparticles having a specific surface area of 100 nm to 200 nm in a dispersion medium containing an organic solvent using a bead mill to obtain an organic solvent dispersion; and (b) adding methyltrimethoxysilane, phenyltrimethoxysilane, methyltriethoxysilane, methacryloxypropyltrimethoxysilane and / or hydrolysates thereof to the organic solvent dispersion obtained in step (a) so that the mass ratio of the organosilicon compound to the forsterite microparticles (organosilicon compound / forsterite microparticles) is 0.01 to 0.50, thereby bonding methyltrimethoxysilyl groups, phenyltrimethoxysilyl groups, methyltriethoxysilyl groups, and methacryloxypropyltrimethoxysilyl groups to the surfaces of the forsterite microparticles. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2016-222517 A [Patent Document 2] JP 2020-100561 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, knowledge about conventional forsterite particles and their manufacturing methods is limited, and there is still room for further study.
[0008] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide forsterite particles having excellent properties and a method for producing the forsterite particles. [Means for solving the problem]
[0009] As a result of intensive research aimed at solving the above problems, the inventors discovered that by using a molybdenum compound as a flux, forsterite particles can be easily produced, and that forsterite particles containing molybdenum can be produced, thereby completing the present invention. That is, the present invention has the following aspects.
[0010] (1) Forsterite grains containing molybdenum. (2) Forsterite particles according to (1), wherein the molybdenum content in the forsterite particles is 0.05 to 35 mass% in terms of MoO3 content (Mo1) relative to 100 mass% of the forsterite particles, as determined by XRF analysis of the forsterite particles. (3) Forsterite particles according to (1) or (2), wherein the molybdenum content in the surface layer of the forsterite particle is 0.05 to 25 mass% in terms of MoO3 content (Mo2) relative to 100 mass% of the surface layer of the forsterite particle, as determined by XPS surface analysis of the forsterite particle. (4) Forsterite particles according to any one of (1) to (3), wherein the average particle size of the primary particles of the forsterite particles is 0.1 to 100 μm. (5) The specific surface area measured by the BET method is 0.02 to 20 m 2 / g. (6) A method for producing forsterite particles according to any one of (1) to (5) above, comprising firing a magnesium compound, and silicon or a silicon compound in the presence of a molybdenum compound. (7) The method for producing forsterite particles according to (6) above, wherein the molybdenum compound is at least one compound selected from the group consisting of molybdenum trioxide, lithium molybdate, potassium molybdate, and sodium molybdate. (8) The method for producing forsterite particles according to (6) or (7) above, wherein the sintering temperature is 800 to 1600° C. (9) The method for producing forsterite particles according to any one of (6) to (8), wherein the molar ratio (Mo / (Mg+Si)) of molybdenum atoms to magnesium and silicon atoms in the raw materials to be fired is 0.001 to 5. Effect of the Invention
[0011] According to the present invention, it is possible to provide forsterite particles having excellent properties and a method for producing the forsterite particles. [Brief description of the drawings]
[0012] [Figure 1] 1 is an SEM image of forsterite particles of Example 1. [Diagram 2] 1 is an SEM image of forsterite particles of Example 2. [Diagram 3] 1 is an SEM image of forsterite particles of Example 3. [Figure 4] 1 is an SEM image of forsterite particles of Example 4. [Diagram 5] 1 is an SEM image of forsterite particles of Example 5. [Figure 6] 1 is an SEM image of forsterite particles of Example 6. [Figure 7] 1 is an SEM image of forsterite particles of Example 7. [Figure 8] 1 is an SEM image of forsterite particles of Example 8. [Figure 9] 1 is an SEM image of forsterite particles of Example 9. [Figure 10] 1 is an SEM image of forsterite particles in Comparative Example 1. [Figure 11] 1 is an SEM image of forsterite particles in Comparative Example 2. [Figure 12] 1 shows X-ray diffraction (XRD) patterns of forsterite particles of Examples 1 to 9 and Comparative Examples 1 and 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, embodiments of the forsterite particles and the method for producing the forsterite particles of the present invention will be described.
[0014] <Forsterite particles> The forsterite particles of the embodiment contain molybdenum. The forsterite particles of the embodiment contain molybdenum and have excellent properties such as catalytic activity derived from molybdenum.
[0015] Furthermore, the forsterite grains of the embodiment can have an excellent property that the grain shape is controlled.
[0016] Additionally, the forsterite particles of the embodiment may have excellent properties of low degree of agglomeration or no agglomeration.
[0017] The forsterite particles of the embodiment may contain molybdenum derived from a molybdenum compound used in the manufacturing method described later. In addition, by using a molybdenum compound in the manufacturing method described later, it is possible to control the particle shape of the manufactured forsterite particles, reduce the content of impurities, and easily manufacture forsterite particles with a low degree of aggregation.
[0018] The state and amount of molybdenum contained in the forsterite particles of the embodiment are not particularly limited, and may be contained in the forsterite particles as molybdenum metal, molybdenum oxide, a partially reduced molybdenum compound, etc. Molybdenum is considered to be contained in the forsterite particles as MoO3, but may also be contained in the forsterite particles as MoO2, MoO, etc. other than MoO3.
[0019] The form in which molybdenum is contained is not particularly limited, and may be contained in a form attached to the surface of the forsterite grains, may be contained in a form substituted as part of the crystal structure of the forsterite grains, may be contained in an amorphous state, or may be a combination of these.
[0020] In this specification, controlling the particle shape of forsterite particles means that the particle shape of the produced forsterite particles is not amorphous. In this specification, forsterite particles with a controlled particle shape mean forsterite particles whose particle shape is not amorphous.
[0021] The forsterite particles of the embodiment may have a polygonal shape. The forsterite particles of the embodiment may have a controlled crystal shape and have an idiomorphic polygonal shape. The forsterite particles with a controlled crystal shape can be produced by the method for producing forsterite particles of the embodiment described later.
[0022] The forsterite particle aggregate (powder) may contain forsterite particles of any shape other than polygonal in any state. The content of polygonal forsterite particles is preferably 80% or more, more preferably 90% or more, and even more preferably 95% or more, based on mass or number, relative to the total amount of the forsterite particle aggregate (powder). The shape of the forsterite particles can be confirmed by a scanning electron microscope (SEM).
[0023] In the manufacturing method of the forsterite particles of the embodiment described below, the particle size and molybdenum content of the obtained forsterite particles can be controlled by controlling the amount and type of the molybdenum compound used as the raw material, the firing temperature, and the like.
[0024] The average particle size of the primary particles of the forsterite particles in the embodiment may be 0.1 to 100 μm, 0.2 to 50 μm, or 0.3 to 40 μm.
[0025] The average particle size of the primary particles of the forsterite particles is calculated as a converted particle size based on the specific surface area described below, assuming that the particles are spherical. The following conversion formula is used. Primary particle diameter Dsa[nm]=6000 / (density[g / cm 3 ] × specific surface area [m2 / g])
[0026] The median diameter D of the forsterite particles of the embodiment calculated by a laser diffraction / scattering method 50 The thickness may be 0.1 to 100 μm, may be 0.2 to 50 μm, or may be 0.3 to 40 μm.
[0027] The median diameter D of the forsterite grain sample calculated by the laser diffraction / scattering method 50 can be calculated as the particle size at which the volume cumulative percentage is 50% in the particle size distribution measured in a dry state using a laser diffraction particle size distribution analyzer.
[0028] The specific surface area of the forsterite particles according to the embodiment, as determined by the BET method, is 0.02 to 20 m 2 / g, and may be 0.04 to 18m 2 / g, and may be 0.05 to 15m 2 / g.
[0029] The specific surface area is measured using a specific surface area meter (e.g., BELSORP-mini, manufactured by Microtrack-Bell Corporation), and the surface area per 1 g of the sample measured from the amount of nitrogen gas adsorbed by the BET method (Brunauer-Emmett-Teller method) is defined as the specific surface area (m 2 / g).
[0030] The forsterite grains of the embodiment include forsterite.
[0031] The forsterite particles of the embodiment preferably contain 65 mass% or more of Mg2SiO4, preferably 65 to 99.95 mass%, more preferably 70 to 99.5 mass%, and even more preferably 75 to 99 mass%, relative to 100 mass% of the forsterite particles.
[0032] The magnesium content in the forsterite particles can be measured by XRF analysis. The magnesium content in the forsterite particles of the embodiment is preferably 30 to 80 mass%, more preferably 35 to 70 mass%, and even more preferably 40 to 66 mass%, in terms of MgO content (Mg1) relative to 100 mass% of the forsterite particles, as determined by XRF analysis of the forsterite particles.
[0033] The silicon content in the forsterite particles can be measured by XRF analysis. The silicon content in the forsterite particles of the embodiment is preferably 10 to 60 mass%, more preferably 15 to 50 mass%, and even more preferably 20 to 45 mass%, as a content (S1) calculated as SiO2 relative to 100 mass% of the forsterite particles, determined by XRF analysis of the forsterite particles.
[0034] The forsterite particles of the embodiment contain molybdenum. The molybdenum content in the forsterite particles can be measured by XRF analysis. The molybdenum content in the forsterite particles of the embodiment is preferably 0.05 mass% or more, more preferably 0.05 to 35 mass%, more preferably 0.08 to 30 mass%, and even more preferably 0.09 to 25 mass%, in terms of MoO3 content (Mo1) relative to 100 mass% of the forsterite particles, determined by XRF analysis of the forsterite particles.
[0035] In the forsterite particles of the embodiment, the upper and lower limit values of the contents (Mg1), (S1), and (Mo1) exemplified above can be freely combined. In addition, the values of the contents (Mg1), (S1), and (Mo1) can also be freely combined.
[0036] As an example of the forsterite particles of the embodiment, the forsterite particles are subjected to XRF analysis, and the forsterite particles are subjected to XRF analysis. The forsterite particles may have a content (Mg1) of 30 to 80 mass%, a content (S1) of 10 to 60 mass%, and a content (Mo1) of 0.05 to 35 mass%, Forsterite particles having a content (Mg1) of 35 to 70 mass%, a content (S1) of 15 to 50 mass%, and a content (Mo1) of 0.08 to 30 mass%, The forsterite particles may have a content (Mg1) of 40 to 66 mass%, a content (S1) of 20 to 45 mass%, and a content (Mo1) of 0.09 to 25 mass%.
[0037] For the above-mentioned XRF analysis, an X-ray fluorescence analyzer (for example, Primus IV manufactured by Rigaku Corporation) can be used.
[0038] The content (Mg1) calculated as MgO refers to the value calculated from the amount of MgO calculated by converting the magnesium content determined by XRF analysis of forsterite particles using a calibration curve calculated as MgO.
[0039] The content (S1) in terms of SiO2 refers to the value obtained by converting the silicon content determined by XRF analysis of forsterite grains into the amount of SiO2 using a calibration curve in terms of SiO2.
[0040] The content (Mo1) in terms of MoO3 refers to the value obtained from the amount of MoO3 converted by using a calibration curve in terms of MoO3 to convert the molybdenum content determined by XRF analysis of forsterite grains.
[0041] The magnesium content in the surface layer of the forsterite particle can be measured by XPS (X-ray photoelectron spectroscopy) surface analysis. The magnesium content in the surface layer of the forsterite particle of the embodiment is preferably 1 to 70 mass%, more preferably 3 to 60 mass%, and even more preferably 5 to 50 mass%, in terms of MgO content (Mg2) relative to 100 mass% of the surface layer of the forsterite particle, as determined by XPS surface analysis of the forsterite particle.
[0042] The silicon content in the surface layer of the forsterite particle can be measured by XPS (X-ray photoelectron spectroscopy) surface analysis. The silicon content in the surface layer of the forsterite particle of the embodiment is preferably 1 to 70 mass%, more preferably 3 to 60 mass%, and even more preferably 5 to 50 mass%, in terms of SiO2 content (S2) relative to 100 mass% of the surface layer of the forsterite particle, as determined by XPS surface analysis of the forsterite particle.
[0043] The molybdenum content in the surface layer of the forsterite particle can be measured by XPS (X-ray photoelectron spectroscopy) surface analysis. The molybdenum content in the surface layer of the forsterite particle of the embodiment is preferably 0.05 mass% or more, more preferably 0.05 to 25 mass%, more preferably 0.08 to 20 mass%, and even more preferably 0.1 to 15 mass%, in terms of MoO3 content (Mo2) relative to 100 mass% of the surface layer of the forsterite particle, as determined by XPS surface analysis of the forsterite particle.
[0044] In the forsterite particles of the embodiment, the upper and lower limit values of the contents (Mg2), (S2), and (Mo2) exemplified above can be freely combined. The values of the contents (Mg2), (S2), and (Mo2) can also be freely combined.
[0045] As an example of the forsterite particle of the embodiment, the following is determined by XPS analysis of the forsterite particle: The forsterite particles may have a content (Mg2) of 1 to 70% by mass, a content (S2) of 1 to 70% by mass, and a content (Mo2) of 0.05 to 25% by mass, The forsterite particles may have a content (Mg2) of 3 to 60 mass%, a content (S2) of 3 to 60 mass%, and a content (Mo2) of 0.08 to 20 mass%, The forsterite particles may have a content (Mg2) of 5 to 50 mass %, a content (S2) of 5 to 50 mass %, and a content (Mo2) of 0.1 to 15 mass %.
[0046] For the above-mentioned XPS analysis, a scanning X-ray photoelectron spectrometer (for example, QUANTERA SXM manufactured by ULVAC-PHI, Inc.) can be used.
[0047] The above content (Mg2) refers to the value obtained by performing XPS surface analysis of forsterite particles using X-ray photoelectron spectroscopy (XPS) to obtain the abundance ratio (atom%) of each element, and converting the magnesium content into oxide to obtain the MgO content relative to 100% by mass of the surface layer of the forsterite particle.
[0048] The above content (S2) refers to the value obtained by performing XPS surface analysis of the forsterite particles using X-ray photoelectron spectroscopy (XPS) to obtain the abundance ratio (atom%) of each element, and converting the silicon content into oxide to obtain the SiO2 content relative to 100 mass% of the surface layer of the forsterite particle.
[0049] The above content (Mo2) refers to the value obtained by performing XPS surface analysis of forsterite particles using X-ray photoelectron spectroscopy (XPS) to obtain the abundance ratio (atom%) of each element, and converting the molybdenum content into an oxide to obtain the MoO3 content relative to 100% by mass of the surface layer of the forsterite particle.
[0050] In the forsterite grain of the embodiment, the molybdenum is preferably unevenly distributed in a surface layer of the forsterite grain.
[0051] Here, in this specification, the term "surface layer" refers to a region within 10 nm from the surface of the forsterite particle of the embodiment. This distance corresponds to the detection depth of the XPS used in the measurements in the examples.
[0052] Here, "distributed unevenly in the surface layer" refers to a state in which the mass of molybdenum or molybdenum compounds per unit volume in the surface layer is greater than the mass of molybdenum or molybdenum compounds per unit volume in areas other than the surface layer.
[0053] In the forsterite particles of this embodiment, molybdenum is concentrated in the surface layer of the forsterite particles, as shown in the examples described later, which can be confirmed by the fact that the molybdenum content (Mo2) in MoO3 equivalent for 100% by mass of the surface layer of the forsterite particles, determined by XPS surface analysis of the forsterite particles, is greater than the molybdenum content (Mo1) in MoO3 equivalent for 100% by mass of the forsterite particles, determined by XRF (X-ray fluorescence) analysis of the forsterite particles.
[0054] In the forsterite particles of the embodiment, as an indicator that molybdenum is concentrated in the surface layer of the forsterite particles, the forsterite particles of the embodiment may have a surface layer concentration ratio of molybdenum (Mo2 / Mo1), which is the content (Mo2) in MoO3 equivalent relative to 100 mass% of the surface layer of the forsterite particle, determined by XPS surface analysis of the forsterite particles, of 1.1 or more, or may be 1.1 to 10.
[0055] By distributing molybdenum or a molybdenum compound unevenly on the surface layer of the forsterite particles, excellent properties such as catalytic activity can be imparted more efficiently than when molybdenum or a molybdenum compound is present not only on the surface layer but also uniformly in the non-surface layer (inner layer).
[0056] The forsterite particles of the embodiment can be provided as an aggregate of forsterite particles, and the above-mentioned magnesium content, silicon content, and molybdenum content values can be values determined by using the aggregate as a sample.
[0057] The forsterite grains of the present embodiment may further contain lithium, potassium, or sodium in addition to molybdenum.
[0058] <Method of manufacturing forsterite particles> The method for producing forsterite particles according to the embodiment includes calcining a magnesium compound and a silicon or silicon compound in the presence of a molybdenum compound. More specifically, the method for producing forsterite particles according to the embodiment may include mixing a magnesium compound, silicon or a silicon compound, and a molybdenum compound to form a mixture, and calcining the mixture.
[0059] By calcining a magnesium compound and silicon or a silicon compound in the presence of a molybdenum compound, the reaction efficiency of forsterite particle production can be improved compared to the case where a molybdenum compound is not used, so that high-quality forsterite particles with a reduced content of impurities can be efficiently produced, and further, forsterite particles with a low degree of aggregation can be easily produced.
[0060] In addition, the use of a compound containing silicon and magnesium, such as magnesium silicate, is also considered to be the use of a magnesium compound and a silicon compound. However, from the viewpoint that the use of a molybdenum compound allows the synthesis reaction to proceed smoothly even in the case of a composite oxide such as forsterite (magnesium silicate), it is preferable that the magnesium compound and silicon compound of the raw material do not include magnesium silicate.
[0061] In addition, the use of a compound containing molybdenum and magnesium, such as magnesium molybdate, is also considered to be the use of a molybdenum compound and a magnesium compound.
[0062] In addition, the use of a compound containing silicon and molybdenum, such as molybdenum silicide, is also considered to be the use of a silicon compound and a molybdenum compound.
[0063] According to the method for producing forsterite particles of the embodiment, it is possible to produce the forsterite particles of the embodiment described above.
[0064] A preferred method for producing forsterite particles includes a step of mixing a magnesium compound, silicon or a silicon compound, and a molybdenum compound to prepare a mixture (mixing step), and a step of firing the mixture (firing step).
[0065] [Mixing process] The mixing step is a step of mixing a magnesium compound, silicon or a silicon compound, and a molybdenum compound to obtain a mixture. The contents of the mixture will be described below.
[0066] (Magnesium compounds) The type of the magnesium compound is not particularly limited. For example, the magnesium compound may be magnesium hydroxide, magnesium oxide, magnesium carbonate, magnesium molybdate, magnesium silicate, magnesium acetate, magnesium chloride, magnesium nitrate, magnesium sulfate, etc., among which magnesium hydroxide or magnesium carbonate is preferred from the viewpoint of ease of reaction, and magnesium hydroxide is more preferred from the viewpoint of the generated gas being water, which is easy to handle.
[0067] Since the shape of the forsterite particles after sintering hardly reflects the shape of the raw magnesium compound, for example, spherical, amorphous, aspected structures (wires, fibers, ribbons, tubes, etc.), sheets, etc. can be suitably used as the magnesium compound.
[0068] (Silicon or silicon compounds) The type of silicon or silicon compound is not particularly limited, and any known silicon compound, including silicon atoms, can be used.Specific examples of these include silica (SiO2), magnesium silicate, molybdenum silicide, silicomolybdic acid, metallic silicon (silicon atom), organic silane compounds, silicone resins, silica particles, silica gel, mesoporous silica, SiC, mullite, and other artificially synthesized silicon compounds; natural silicon compounds such as biosilica.
[0069] The shape of silicon or a silicon compound containing elemental silicon is not particularly limited, and for example, a sphere, an amorphous shape, an aspected structure (wire, fiber, ribbon, tube, etc.), a sheet, etc. can be suitably used.
[0070] (Molybdenum Compounds) Examples of the molybdenum compound include molybdenum oxide, molybdic acid, molybdenum sulfide, molybdenum silicide, silicomolybdic acid, magnesium molybdate, and molybdate compounds, with molybdenum oxide and molybdate compounds being preferred.
[0071] The molybdenum oxide includes molybdenum dioxide (MoO2), molybdenum trioxide (MoO3), etc., with molybdenum trioxide being preferred.
[0072] The molybdate compound is MoO4 2- , Mo2O7 2- , Mo3O 10 2- , Mo4O 13 2- , Mo5O 16 2- , Mo6O 19 2- , Mo7O 24 6- , Mo8O 26 4- The molybdenum oxoanion may be, but is not limited to, a salt compound of the molybdenum oxoanion such as those mentioned above. The molybdenum oxoanion may be an alkali metal salt, an alkaline earth metal salt, or an ammonium salt.
[0073] The molybdate compound is preferably an alkali metal salt of a molybdenum oxoanion, more preferably lithium molybdate, potassium molybdate or sodium molybdate, even more preferably potassium molybdate or sodium molybdate, and particularly preferably sodium molybdate.
[0074] In the method for producing forsterite particles of the present embodiment, the molybdate compound may be a hydrate.
[0075] The molybdenum compound is preferably at least one compound selected from the group consisting of molybdenum trioxide, lithium molybdate, potassium molybdate, and sodium molybdate, more preferably at least one compound selected from the group consisting of molybdenum trioxide, potassium molybdate, and sodium molybdate, and further preferably molybdenum trioxide and / or sodium molybdate.
[0076] In the manufacturing method of the embodiment, the use of the above-mentioned molybdate compound tends to reduce the molybdenum content of the produced forsterite particles, which is preferable from the viewpoint of increasing the crystallinity of the forsterite.
[0077] The method for producing forsterite particles according to the embodiment may include a step of calcining a magnesium compound and silicon or a silicon compound in the presence of a molybdenum compound and a sodium compound and / or a potassium compound.
[0078] The method for producing forsterite particles of the embodiment may include a step (mixing step) of mixing a magnesium compound, a silicon or silicon compound, a molybdenum compound, and a sodium compound and / or a potassium compound to form a mixture prior to the firing step, and may include a step (firing step) of firing the mixture.
[0079] In the manufacturing method of the embodiment, by using a sodium compound and / or a potassium compound, it is easy to adjust the particle size of the forsterite particles produced, and it is possible to easily produce forsterite particles with little or no aggregation.
[0080] Here, at least a part of the molybdenum compound and the sodium compound may be replaced with a compound containing molybdenum and sodium, such as sodium molybdate, and at least a part of the molybdenum compound and the potassium compound may be replaced with a compound containing molybdenum and potassium, such as potassium molybdate.
[0081] Therefore, a process of mixing a magnesium compound, silicon or a silicon compound, and a compound containing molybdenum and potassium and / or sodium to obtain a mixture is also considered to be a process of mixing a magnesium compound, silicon or a silicon compound, a molybdenum compound, and a potassium compound and / or a sodium compound to obtain a mixture.
[0082] In addition, a compound containing molybdenum and sodium suitable as a fluxing agent can be produced, for example, in the process of firing using a molybdenum compound and a sodium compound, which are less expensive and more readily available, as raw materials. Here, the use of a molybdenum compound and a sodium compound as fluxing agents and the use of a compound containing molybdenum and sodium as fluxing agents are both considered to be the use of a molybdenum compound and a sodium compound as fluxing agents, i.e., in the presence of a molybdenum compound and a sodium compound.
[0083] A compound containing molybdenum and potassium suitable as a fluxing agent can be produced, for example, in the firing process using a molybdenum compound and a potassium compound, which are cheaper and more readily available, as raw materials. Here, the use of a molybdenum compound and a potassium compound as fluxing agents and the use of a compound containing molybdenum and potassium as fluxing agents are both considered to be the use of a molybdenum compound and a potassium compound as fluxing agents, i.e., in the presence of a molybdenum compound and a potassium compound.
[0084] The above-mentioned molybdenum compounds may be used alone or in combination of two or more kinds.
[0085] In addition, sodium molybdate (Na2Mo n O 3n+1 , n=1 to 3) contains sodium and can therefore function as a sodium compound, which will be described later.
[0086] In addition, potassium molybdate (K2Mon O 3n+1 , n=1 to 3) contains potassium and can therefore also function as a potassium compound, which will be described later.
[0087] (Sodium compounds) The sodium compound is not particularly limited, but examples thereof include sodium carbonate, sodium molybdate, sodium oxide, sodium sulfate, sodium hydroxide, sodium nitrate, sodium chloride, metallic sodium, etc. Among these, it is preferable to use sodium carbonate, sodium molybdate, sodium oxide, and sodium sulfate from the viewpoints of industrial ease of availability and ease of handling.
[0088] The above-mentioned sodium compounds may be used alone or in combination of two or more kinds.
[0089] As described above, sodium molybdate contains molybdenum and can therefore function as the molybdenum compound described above.
[0090] (Potassium compounds) The potassium compound is not particularly limited, but includes potassium chloride, potassium chlorite, potassium chlorate, potassium sulfate, potassium hydrogen sulfate, potassium sulfite, potassium hydrogen sulfite, potassium nitrate, potassium carbonate, potassium hydrogen carbonate, potassium acetate, potassium oxide, potassium bromide, potassium bromate, potassium hydroxide, potassium silicate, potassium phosphate, potassium hydrogen phosphate, potassium sulfide, potassium hydrogen sulfide, potassium molybdate, potassium tungstate, etc. In this case, the potassium compound includes isomers, as in the case of molybdenum compounds. Among these, it is preferable to use potassium carbonate, potassium hydrogen carbonate, potassium oxide, potassium hydroxide, potassium chloride, potassium sulfate, and potassium molybdate, and it is more preferable to use potassium carbonate, potassium hydrogen carbonate, potassium chloride, potassium sulfate, and potassium molybdate.
[0091] The potassium compounds described above may be used alone or in combination of two or more kinds.
[0092] As described above, potassium molybdate contains molybdenum and can therefore function as the molybdenum compound described above.
[0093] In the method for producing forsterite particles according to the embodiment, a preferred combination of raw materials is magnesium hydroxide, silicon dioxide, and molybdenum trioxide.
[0094] Similarly, a preferred combination of raw materials in the method for producing forsterite particles according to the embodiment is the use of magnesium hydroxide, silicon dioxide, and sodium molybdate or a hydrate thereof.
[0095] Similarly, a preferred combination of raw materials in the method for producing forsterite particles according to the embodiment includes magnesium hydroxide, silicon dioxide, molybdenum trioxide, and sodium molybdate or a hydrate thereof.
[0096] By firing a magnesium compound and a silicon or silicon compound in the presence of a molybdenum compound and a sodium compound, or in the presence of a molybdenum compound and a potassium compound, it is easy to adjust the particle size of the produced forsterite particles, and it is easy to produce forsterite particles with little or no aggregation. The reason is not clear, but the following reasons are considered. For example, K2MoO4 and Na2MoO4 are stable compounds and are difficult to volatilize during the firing process, so they are unlikely to undergo rapid reactions during the volatilization process, making it easy to control the growth of forsterite particles. It is also considered that the molten K2MoO4 and Na2MoO4 function like a solvent, and the particle size value can be increased, for example, by extending the reaction time. It is also considered that the molten K2MoO4 and Na2MoO4 function like a solvent, so that the forsterite particles are dispersed and aggregation is unlikely to occur.
[0097] In the method for producing forsterite particles of this embodiment, a molybdenum compound is used as a fluxing agent. In the present specification, this method using a molybdenum compound as a fluxing agent may be simply referred to as a "flux method". In addition, after the magnesium compound, silicon or a silicon compound, and a molybdenum compound react with each other at high temperatures by the firing to form magnesium molybdate and silicomolybdic acid, it is considered that when the magnesium molybdate and silicomolybdic acid are further decomposed at high temperatures into magnesium oxide and molybdenum oxide, and silicon oxide and molybdenum oxide, some of the molybdenum oxide is taken into the forsterite particles. Most of the molybdenum oxide is evaporated and removed from the system, but when sodium molybdate or potassium molybdate is used as the molybdenum compound, the alkali metal compound and molybdenum oxide are easily combined to form a molybdate salt again, which is hardly discharged outside the system and remains in the system.
[0098] Regarding the mechanism of formation of the molybdenum compounds contained in the forsterite particles, more specifically, Mg atoms and Si atoms react to form Mo-O-Mg and Mo-O-Si in the forsterite particles, and while most of the Mo is released by high-temperature sintering, it is believed that some molybdenum remains in the particles in the form of Mo-O-Mg and Mo-O-Si.
[0099] Molybdenum oxide that is not incorporated into the forsterite particles can be recovered and reused by sublimation, which reduces the amount of molybdenum oxide that adheres to the surfaces of the forsterite particles and maximizes the inherent properties of the forsterite particles.
[0100] On the other hand, the alkali metal salt of the molybdenum oxoanion does not vaporize even at the calcination temperature range and can be easily recovered by washing after calcination. This reduces the amount of molybdenum compounds released outside the calcination furnace, and also allows for a significant reduction in production costs.
[0101] In the above flux method, for example, when a molybdenum compound and a sodium compound are used in combination, it is believed that the molybdenum compound and the sodium compound react to form sodium molybdate. At the same time, the molybdenum compound reacts with a magnesium compound and a silicon compound to form magnesium molybdate and silicomolybdic acid, and then, by further high-temperature firing, these magnesium molybdate and silicomolybdic acid are decomposed and then forsterite is formed. Then, for example, by decomposing magnesium molybdate and silicomolybdic acid in the presence of liquid-phase sodium molybdate to form forsterite and then growing the crystal, it is believed that the evaporation of the above flux (sublimation of MoO3) can be suppressed, and forsterite particles with low or no aggregation can be easily obtained.
[0102] (metal compound) A metal compound can be used during firing if desired. The method for producing forsterite particles according to the embodiment can include a step (mixing step) of mixing a magnesium compound, a silicon or silicon compound, a molybdenum compound, a sodium compound and / or a potassium compound, and a metal compound to form a mixture prior to the firing step, and can include a step (firing step) of firing the mixture.
[0103] The metal compound is not particularly limited, but preferably contains at least one selected from the group consisting of Group II metal compounds and Group III metal compounds.
[0104] Examples of the Group II metal compound include calcium compounds, strontium compounds, and barium compounds.
[0105] Examples of the Group III metal compound include a scandium compound, an yttrium compound, a lanthanum compound, and a cerium compound.
[0106] The above-mentioned metal compounds refer to oxides, hydroxides, carbonates, and chlorides of metal elements. For example, yttrium compounds include yttrium oxide (Y2O3), yttrium hydroxide, and yttrium carbonate. Of these, the metal compounds are preferably oxides of metal elements. These metal compounds include isomers.
[0107] Among these, the metal compounds of the third periodic elements, the metal compounds of the fourth periodic elements, the metal compounds of the fifth periodic elements, and the metal compounds of the sixth periodic elements are preferred, the metal compounds of the fourth periodic elements and the metal compounds of the fifth periodic elements are more preferred, and the metal compounds of the fifth periodic elements are even more preferred. Specifically, it is preferred to use calcium compounds, yttrium compounds, and lanthanum compounds, it is more preferred to use calcium compounds and yttrium compounds, and it is particularly preferred to use yttrium compounds.
[0108] The metal compound is preferably used in a proportion of, for example, 0 to 1.2 mass % (for example, 0 to 1 mol %) relative to the total amount of the magnesium compounds used in the mixing step.
[0109] In the method for producing forsterite particles of this embodiment, the amounts of the magnesium compound, silicon or silicon compound, and molybdenum compound used are not particularly limited, but in the raw materials, for example in the mixture, the molybdenum compound may be blended in an amount of 1 to 500 parts by mass, or 5 to 200 parts by mass, per 100 parts by mass of the total amount of the magnesium compound and silicon or silicon compound.
[0110] In the method for producing forsterite particles of this embodiment, the molar ratio of magnesium to silicon (Mg / Si) in the raw material, for example in the mixture, is basically 2, and since any excess MgO that may be produced can be easily removed, the Mg / Si may be 2 or more, may be 2 to 3, or may be 2 to 2.5.
[0111] In the embodiment of the method for producing forsterite particles, the molar ratio (molybdenum / (magnesium + silicon)) of molybdenum atoms in the molybdenum compound to magnesium and silicon atoms in the magnesium compound and silicon compound in the raw materials, for example in the mixture, is preferably 0.001 or more, more preferably 0.01 or more, even more preferably 0.02 or more, and particularly preferably 0.04 or more.
[0112] The upper limit of the molar ratio of molybdenum atoms in the molybdenum compound to magnesium and silicon atoms in the magnesium compound and silicon compound in the raw materials, for example, in the mixture, may be determined as appropriate. From the viewpoint of reducing the amount of molybdenum compound used and improving production efficiency, for example, the molar ratio (molybdenum / (magnesium+silicon)) may be 5 or less, 3 or less, 1 or less, or 0.5 or less.
[0113] An example of the numerical range of the molar ratio (molybdenum / (magnesium + silicon)) in the raw material, for example, in the mixture, is that the value of molybdenum / (magnesium + silicon) may be 0.001 to 5, 0.01 to 3, 0.02 to 1, or 0.04 to 0.5.
[0114] As the amount of molybdenum used relative to magnesium and silicon increases, there is a tendency for forsterite particles having a larger particle size, as shown in Table 2 in the examples described later, to be obtained according to the above particle size distribution.
[0115] By using various compounds within the above ranges, the amount of molybdenum compound contained in the obtained forsterite particles becomes more appropriate, and forsterite particles with controlled particle shape and size can be easily obtained.
[0116] [Firing process] The firing step is a step of firing the mixture. The forsterite particles according to the embodiment are obtained by firing the mixture. As described above, this manufacturing method is called a flux method.
[0117] The flux method is classified as a solution method. More specifically, the flux method is a crystal growth method that utilizes the fact that the crystal-flux two-component phase diagram shows a eutectic type. The mechanism of the flux method is presumed to be as follows. That is, when a mixture of a solute and flux is heated, the solute and flux become liquid phase. At this time, since the flux is a flux, in other words, since the solute-flux two-component phase diagram shows a eutectic type, the solute melts at a temperature lower than its melting point and forms a liquid phase. If the flux is evaporated in this state, the concentration of the flux decreases, in other words, the effect of the flux in lowering the melting point of the solute is reduced, and the evaporation of the flux becomes the driving force to cause crystal growth of the solute (flux evaporation method). The solute and flux can also cause crystal growth of the solute by cooling the liquid phase (slow cooling method).
[0118] The flux method has the advantages of being able to grow crystals at temperatures much lower than the melting point, being able to precisely control the crystal structure, and being able to form idiomorphic crystals.
[0119] In the production of forsterite particles by the flux method using a molybdenum compound as a flux, the mechanism is not necessarily clear, but it is assumed that, for example, the following mechanism is involved. That is, when a magnesium compound and a silicon compound are fired in the presence of a molybdenum compound, magnesium molybdate and silicomolybdic acid are first formed. At this time, as can be understood from the above explanation, the magnesium molybdate and silicomolybdic acid grow forsterite crystals at a temperature lower than the melting point of forsterite. Then, for example, by evaporating the flux, the magnesium molybdate and silicomolybdic acid are decomposed, and the crystals grow, thereby obtaining forsterite particles. That is, the molybdenum compound functions as a flux, and forsterite particles are produced via intermediates such as magnesium molybdate and silicomolybdic acid.
[0120] By the above-mentioned flux method, it is possible to produce forsterite particles that contain molybdenum and in which the molybdenum is unevenly distributed in the surface layer of the forsterite particles.
[0121] The firing method is not particularly limited, and can be performed by a known conventional method. It is considered that the magnesium compound, silicon or a silicon compound, and a molybdenum compound react with each other during the firing process to form magnesium molybdate and silicomolybdic acid. Furthermore, it is considered that when the firing temperature is 700°C or higher, magnesium molybdate and silicomolybdic acid decompose to form forsterite particles. In addition, in the forsterite particles, magnesium molybdate and silicomolybdic acid decompose to form magnesia, silica, and molybdenum oxide, and then when forsterite is formed, the molybdenum compound is taken into the forsterite particles.
[0122] In addition, the state of the magnesium compound, silicon or silicon compound, and molybdenum compound during firing is not particularly limited, and the molybdenum compound may be present in the same space where it can act on the magnesium compound and the silicon or silicon compound. Specifically, the molybdenum compound powder, the magnesium compound powder, and the silicon or silicon compound powder may be simply mixed together, mechanically mixed using a grinder or the like, or mixed using a mortar or the like, or may be mixed in a dry state or a wet state.
[0123] The firing temperature condition is not particularly limited, and is appropriately determined in consideration of the target particle size of forsterite particles, the formation of molybdenum compounds in the forsterite particles, the shape of the forsterite particles, etc. The firing temperature may be 700°C or higher, which is close to the decomposition temperature of magnesium molybdate and silicomolybdic acid, 800°C or higher, 900°C or higher, 950°C or higher, or 1000°C or higher.
[0124] The higher the firing temperature, the more easily the particle shape is controlled and the larger the particle size of the forsterite particles is obtained. From the viewpoint of efficiently producing such forsterite particles, the firing temperature is preferably 950° C. or higher, more preferably 1000° C. or higher, even more preferably 1100° C. or higher, and particularly preferably 1200° C. or higher.
[0125] Generally, in order to control the shape of forsterite particles obtained after firing, it is necessary to fire the material at high temperatures of over 1800°C, which is close to the melting point of forsterite. However, this poses significant challenges for industrial use due to the burden on the firing furnace and fuel costs.
[0126] According to one embodiment of the present invention, even when the maximum sintering temperature for sintering a magnesium compound and silicon or a silicon compound is 1800°C or lower, forsterite particles can be formed efficiently at low cost, which contributes to reducing energy costs and environmental load.
[0127] Furthermore, according to the method for producing forsterite particles of the embodiment, idiomorphous forsterite particles can be formed regardless of the shape of the precursor even at a firing temperature of 1600° C. or less, which is much lower than the melting point of forsterite. From this viewpoint, the firing temperature is preferably 1500° C. or less, more preferably 1400° C. or less, and even more preferably 1300° C. or less.
[0128] In the firing step, the numerical range of the firing temperature at which the magnesium compound and silicon or the silicon compound are fired may be, for example, 800 to 1600°C, 900 to 1500°C, 950 to 1400°C, or 1000 to 1300°C.
[0129] From the viewpoint of production efficiency, the temperature rise rate may be 20 to 600° C. / h, 40 to 500° C. / h, or 80 to 400° C. / h.
[0130] Regarding the firing time, the time required to raise the temperature to a predetermined firing temperature is preferably within the range of 15 minutes to 10 hours. The holding time at the firing temperature can be 5 minutes or more, and is preferably within the range of 5 minutes to 1000 hours, and more preferably within the range of 1 to 30 hours. In order to efficiently form forsterite particles, it is more preferable to hold the firing temperature for 2 hours or more, and particularly preferably to hold the firing temperature for 2 to 24 hours.
[0131] For example, by selecting conditions of a firing temperature of 800 to 1600° C. and a firing temperature holding time of 2 to 24 hours, forsterite particles of the embodiment containing molybdenum can be easily obtained.
[0132] The firing atmosphere is not particularly limited as long as the effects of the present invention can be obtained. For example, an oxygen-containing atmosphere such as air or oxygen, or an inert atmosphere such as nitrogen, argon, or carbon dioxide is preferable, and an air atmosphere is more preferable in terms of cost.
[0133] The calcination apparatus is not necessarily limited, and a so-called calcination furnace can be used. The calcination furnace is preferably made of a material that does not react with the sublimated molybdenum oxide, and it is preferable to use a highly airtight calcination furnace so as to efficiently utilize the molybdenum oxide.
[0134] [Cooling process] The method for producing forsterite particles may include a cooling step, which is a step of cooling the forsterite particles that have undergone crystal growth in the firing step.
[0135] The cooling rate is not particularly limited, but is preferably 1 to 1000°C / hour, more preferably 5 to 500°C / hour, and even more preferably 50 to 100°C / hour. A cooling rate of 1°C / hour or more is preferable because the manufacturing time can be shortened. On the other hand, a cooling rate of 1000°C / hour or less is preferable because the firing container is less likely to crack due to heat shock and can be used for a long time.
[0136] The cooling method is not particularly limited, and may be natural cooling or a cooling device may be used.
[0137] [Molybdenum removal process] The method for producing forsterite particles according to the present embodiment may further include, after the firing step, a molybdenum removal step of removing at least a portion of molybdenum, as necessary.
[0138] Methods include washing and high temperature treatment, which may be performed in combination.
[0139] As described above, since molybdenum sublimes during firing, the molybdenum content in the surface layer of the forsterite particles can be controlled by controlling the firing time, firing temperature, etc., and the molybdenum content and state of existence in the layers other than the surface layer (inner layer) of the forsterite particles can also be controlled.
[0140] Molybdenum may adhere to the surface of the forsterite grains. As an alternative to sublimation, the molybdenum may be removed by washing with water, an aqueous ammonia solution, an aqueous sodium hydroxide solution, or the like.
[0141] In this case, the molybdenum content in the forsterite particles can be controlled by appropriately changing the concentrations and amounts of water, the aqueous ammonia solution, and the aqueous sodium hydroxide solution used, as well as the washing locations and washing times.
[0142] As a method for high-temperature treatment, a method in which the temperature is raised to the sublimation point or boiling point of the molybdenum compound or higher can be mentioned.
[0143] [Crushing process] In the sintered product obtained through the sintering step, the forsterite particles may aggregate and may not satisfy the suitable particle size range for the intended application. Therefore, the forsterite particles may be pulverized as necessary to satisfy the suitable particle size range. The method for pulverizing the fired product is not particularly limited, and any conventionally known pulverizing method such as a ball mill, a jaw crusher, a jet mill, a disk mill, a spectromill, a grinder, or a mixer mill can be used.
[0144] [Classification process] The sintered product containing forsterite particles obtained by the sintering step may be classified as appropriate to adjust the range of particle sizes. "Classification" refers to an operation of classifying particles into groups according to their sizes.
[0145] The classification may be either a wet type or a dry type, but from the viewpoint of productivity, a dry type classification is preferred. Dry classification includes classification using a sieve as well as wind classification, which classifies based on the difference between centrifugal force and fluid drag. From the viewpoint of classification accuracy, wind classification is preferred, and can be carried out using a classifier such as an air current classifier that utilizes the Coanda effect, a swirling air current classifier, a forced vortex centrifugal classifier, or a semi-free vortex centrifugal classifier.
[0146] The above-mentioned pulverization step and classification step can be carried out at any stage required. Depending on whether or not pulverization or classification is performed and the selection of the conditions therefor, for example, the average particle size of the obtained forsterite particles can be adjusted.
[0147] The forsterite particles of the embodiment, or the forsterite particles obtained by the manufacturing method of the embodiment, have a low degree of aggregation or are not aggregated at all, so that they are more likely to exhibit their inherent properties and are easier to handle. Furthermore, when dispersed in a dispersion medium for use, they are preferable from the viewpoint of having better dispersibility.
[0148] Furthermore, according to the above embodiment of the method for producing forsterite particles, it is possible to easily produce forsterite particles with little or no agglomeration, which has the excellent advantage that forsterite particles having the desired excellent properties can be produced with high productivity without performing the above-mentioned crushing and classification processes.
[0149] According to the method for producing forsterite grains of the embodiment described above, it is possible to produce high-quality forsterite grains that contain molybdenum and have a controlled shape with high efficiency. EXAMPLES
[0150] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to the following examples.
[0151] <Production of forsterite particles> [Example 1] 5.8g of magnesium hydroxide (Kisuma (registered trademark) 5, manufactured by Kyowa Chemical Industry Co., Ltd.), 3.0g of silicon dioxide (VN3, manufactured by Toso Silica Co., Ltd.), 8.8g of sodium molybdate dihydrate (reagent manufactured by Kanto Chemical Co., Ltd.), 30g of ion-exchanged water, and 120g of zirconia beads (5 mm diameter) were charged into a 100 ml polypropylene bottle, mixed and pulverized for 120 minutes using a paint shaker to obtain a mixture. The mixture obtained was transferred to a metal tray and dried in an oven at 120°C, and the dried product was pulverized in a mixer (manufactured by Osaka Chemical Co., Ltd.). The pulverized raw material was placed in a crucible and fired in a ceramic electric furnace at 1500°C for 10 hours. The temperature was raised at a rate of 2°C / min. After the temperature was lowered, the crucible was removed to obtain a white powder.
[0152] The white powder obtained was then transferred to a beaker, 200 g of ion-exchanged water was added, and the mixture was stirred for 3 hours to dissolve sodium molybdate in the ion-exchanged water.Then, the mixture was filtered by suction filtration using 5C filter paper, and the obtained particles were dried at 120°C to obtain 6.8 g of the white powder of Example 1.
[0153] [Example 2] 5.8g of magnesium hydroxide (Kisuma 5, Kyowa Chemical Industry Co., Ltd.), 3.0g of silicon dioxide (VN3, Toso Silica Co., Ltd.), 0.88g of molybdenum trioxide (Nippon Inorganic Chemical Industry Co., Ltd.), and 100g of 5mmφ zirconia beads were charged into an 80ml zirconia pot, and mixed and ground for 60 minutes at 200 rpm using a planetary mill (P-5, Fritsch Co., Ltd.) to obtain a mixture. The resulting mixture was placed in a crucible and fired at 1300°C for 10 hours in a ceramic electric furnace. The temperature was raised at a rate of 2°C / min. After cooling, the crucible was removed and a white powder was obtained.
[0154] The white powder was then transferred to a beaker, 200 g of 0.5% aqueous ammonia was added, and the mixture was stirred for 3 hours to dissolve the remaining molybdenum trioxide in the aqueous ammonia. The mixture was then filtered by suction filtration using 5C filter paper, and the resulting particles were dried at 120° C. to obtain the white powder 6.8 of Example 2.
[0155] [Example 3] A white powder of Example 3 was obtained in the same manner as in Example 1, except that the firing temperature was 1000° C. and the heating rate was 5° C. / min.
[0156] [Example 4] A white powder of Example 4 was obtained in the same manner as in Example 1, except that the firing temperature was 1300° C. and the heating rate was 5° C. / min.
[0157] [Example 5] A white powder of Example 5 was obtained in the same manner as in Example 2, except that the firing temperature was 1100° C. and the heating rate was 5° C. / min.
[0158] [Example 6] 8.28g of magnesium hydroxide (Kisuma 5, manufactured by Kyowa Chemical Industry Co., Ltd.), 4.29g of silicon dioxide (VN3, manufactured by Toso Silica Co., Ltd.), 6.96g of sodium molybdate dihydrate (reagent manufactured by Kanto Chemical Co., Ltd.), 4.11g of molybdenum trioxide (manufactured by Nippon Inorganic Chemical Industry Co., Ltd.), 30g of ion-exchanged water, and 120g of 5mmφ zirconia beads were charged into a 100ml polypropylene bottle, mixed and crushed for 120 minutes using a paint shaker to obtain a mixture. The resulting mixture was transferred to a metal tray and dried in an oven at 120°C, and the dried product was crushed in a mixer (manufactured by Osaka Chemical Co., Ltd.). The crushed raw materials were placed in a crucible and fired at 900°C for 10 hours in a ceramic electric furnace. The temperature was raised at a rate of 5°C / min. After cooling, the crucible was removed and a white powder was obtained.
[0159] The white powder obtained was then transferred to a beaker, 200 g of ion-exchanged water was added, and the mixture was stirred for 3 hours to dissolve sodium molybdate in the ion-exchanged water.Then, the mixture was filtered by suction filtration using 5C filter paper, and the obtained particles were dried at 120°C to obtain 10.2 g of white powder of Example 6.
[0160] [Example 7] A white powder of Example 7 was obtained in the same manner as in Example 6, except that the firing temperature was 1100°C.
[0161] [Example 8] A white powder of Example 8 was obtained in the same manner as in Example 6, except that the firing temperature was 1300°C.
[0162] [Example 9] A white powder of Example 9 was obtained in the same manner as in Example 6, except that the firing temperature was 1500° C. and the heating rate was 2° C. / min.
[0163] [Examples 10 to 13] White powders of Examples 10 to 13 were obtained in the same manner as in Example 4, except that the amount of sodium molybdate dihydrate used in Example 4 was changed to the mass shown in Table 2.
[0164] [Comparative Example 1] 5.8g of magnesium hydroxide (Kisuma 5, manufactured by Kyowa Chemical Industry Co., Ltd.), 3.0g of silicon dioxide (VN3, manufactured by Toso Silica Co., Ltd.), and 100g of 5mmφ zirconia beads were charged into an 80ml zirconia pot, and mixed and pulverized for 60 minutes using a planetary mill (P-5, manufactured by Fritsch Co., Ltd.) to obtain a mixture. The resulting mixture was placed in a crucible and fired at 1100°C for 10 hours in a ceramic electric furnace. The temperature was raised at a rate of 5°C / min. After cooling, the crucible was removed, and a white powder of Comparative Example 1 was obtained.
[0165] [Comparative Example 2] A white powder of Comparative Example 2 was obtained in the same manner as in Comparative Example 1, except that the firing temperature was 1300°C.
[0166] <Evaluation> The powders obtained in each of the Examples and Comparative Examples were used as sample powders and were evaluated as follows.
[0167] [Crystal structure analysis: XRD (X-ray diffraction) method] The sample powder was filled into a measurement sample holder with a depth of 0.5 mm, which was then set into a wide-angle X-ray diffraction (XRD) device (Ultima IV, manufactured by Rigaku Corporation) and measurements were performed under the following conditions: Cu / Kα radiation, 40 kV / 40 mA, scan speed 2° / min, and scan range 10 to 70°.
[0168] [Measurement of specific surface area of forsterite particles] The specific surface area of the forsterite particles was measured using a specific surface area meter (Microtrack-Bel, BELSORP-mini), and the surface area per 1 g of sample measured from the amount of nitrogen gas adsorbed by the BET method was defined as the specific surface area (m 2 / g).
[0169] [Primary particle size] The primary particle diameter of the forsterite particles was calculated as a converted particle diameter based on the specific surface area described above, assuming that the particles were spherical. The following conversion formula was used. Primary particle diameter Dsa[nm]=6000 / (density[g / cm 3 ] × specific surface area [m 2 / g]) In this example, the density of the forsterite grains is 3.0 g / cm 3 The calculation was made as follows.
[0170] [Particle size distribution measurement] The particle size distribution of the sample powder was measured in a dry state using a laser diffraction type dry particle size distribution analyzer (HELOS (H3355) & RODOS, manufactured by Japan Laser Co., Ltd.) under the conditions of a dispersion pressure of 3 bar and a suction pressure of 90 mbar. The particle size at the point where the distribution curve of the volume cumulative percentage intersects with the horizontal axis of 50% was defined as D. 50 was requested as follows.
[0171] [XRF (X-ray fluorescence) analysis] Using a Primus IV X-ray fluorescence analyzer (Rigaku Corporation), approximately 70 mg of sample powder was placed on filter paper, covered with PP film, and XRF (X-ray fluorescence) analysis was performed under the following conditions. Measurement conditions EZ Scan Mode Measuring elements: F~U Measurement time: Standard Measurement diameter: 10mm Balance: None
[0172] The magnesium content, silicon content, and molybdenum content of the forsterite particles obtained by XRF analysis were converted into oxides to obtain the MgO content (Mg1) relative to 100% by mass of the forsterite particles, the SiO2 content (S1) relative to 100% by mass of the forsterite particles, and the MoO3 content (Mo1) relative to 100% by mass of the forsterite particles.
[0173] [XPS surface analysis] Surface elemental analysis of the sample powder was performed using an ULVAC-PHI QUANTERA SXM, with monochromated Al-Kα as the X-ray source, and X-ray photoelectron spectroscopy (XPS: X-ray photoelectron spectroscopy). The area was measured in a 1000 μm square area, and the average value of n=3 measurements was obtained in atom% for each element.
[0174] The magnesium and silicon contents and the molybdenum content in the surface layer of the forsterite particles obtained by XPS analysis were converted into oxides to determine the MgO content (Mg2) (mass %) relative to 100 mass % of the surface layer of the forsterite particle, the SiO2 content (S2) (mass %) relative to 100 mass % of the surface layer of the forsterite particle, and the MoO3 content (Mo2) (mass %) relative to 100 mass % of the surface layer of the forsterite particle.
[0175] <Result> The values obtained by the above evaluations are shown in Tables 1 and 2. Note that "ND" is an abbreviation for "not detected," which indicates that the substance was not detected.
[0176] [Table 1]
[0177] [Table 2]
[0178] FIGS. 1 to 11 show SEM images of the powders of the above-mentioned Examples and Comparative Examples taken with a scanning electron microscope (SEM). In the powders of Examples 1 to 9, many particles with beautiful polygonal shapes were confirmed, and the crystal shape of the particles was controlled during the production process. On the other hand, in the powders of Comparative Examples 1 and 2, amorphous particles with no particular shape were observed.
[0179] The results of the XRD analysis are shown in Figure 12. Peaks (unmarked peaks) derived from forsterite (Mg2SiO4) were observed in the samples of each of the examples and comparative examples.
[0180] From the results of the SEM observation and XRD analysis described above, it was confirmed that the powders obtained in the examples and comparative examples were forsterite particles containing forsterite.
[0181] In the sample powders of Examples 1 to 9, almost no peaks derived from impurities were observed (FIG. 12, impurity detection "-" in Table 1). On the other hand, in the sample powders of Comparative Examples 1 and 2, the peaks (peaks marked with ● in FIG. 12) derived from impurities such as enstatite (MgSiO3) were significantly detected (detection of impurities "+" in Table 1). From this, it was inferred that the reaction of producing forsterite was not completed in the sample powders of Comparative Examples 1 and 2, and unreacted substances remained.
[0182] This shows that in each example in which a magnesium compound and a silicon compound were fired in the presence of a molybdenum compound, even at a relatively low firing temperature of 900°C to 1500°C, the forsterite formation reaction proceeds well, the content of the above-mentioned impurities is reduced, and high-quality forsterite particles with controlled shape can be produced with high efficiency.
[0183] In addition, each forsterite particle was dispersed in ethanol, and then observed with a TEM, and the degree of particle aggregation was evaluated according to the following criteria. +: Particle aggregation is observed. -: No noticeable aggregation of particles is observed.
[0184] In the forsterite particles of Comparative Examples 1 and 2, noticeable aggregation and fusion between particles was observed (degree of aggregation: +), whereas in the forsterite particles of Examples 1 to 9, noticeable aggregation was not observed (degree of aggregation: -).
[0185] This shows that in each example in which a magnesium compound and a silicon compound were sintered in the presence of a molybdenum compound, the reaction proceeded well during sintering, and forsterite particles with little or no agglomeration could be easily produced.
[0186] In addition, when comparing Examples 2 and 4 at the same firing temperature, the forsterite particles obtained in Example 4, which used Na2MoO4·2H2O as the raw material, had a lower degree of aggregation than the forsterite particles obtained in Example 2.
[0187] This shows that forsterite particles with a low degree of aggregation can be easily obtained by firing a magnesium compound and a silicon compound in the presence of sodium molybdate.
[0188] Furthermore, in each Example (see, for example, Examples 1, 3, and 4), there was a tendency that the higher the firing temperature, the larger the particle size of the forsterite particles obtained.
[0189] In this way, it is clear that by controlling the firing temperature, the particle size of the forsterite particles can be controlled, and forsterite particles having a desired particle size can be produced.
[0190] Table 1 shows the values of the above MgO content (Mg1), SiO2 content (S1), MoO3 content (Mo1), MgO content (Mg2), SiO2 content (S2), and MoO3 content (Mo2).
[0191] The results of MoO3 content (Mo1) confirmed that forsterite grains containing molybdenum were obtained.
[0192] From the results of the MoO3 content (Mo2), the forsterite particles of Examples 1 to 9 contain molybdenum in the surface layer, and it is expected that various actions due to molybdenum, such as catalytic activity, will be exhibited.
[0193] Table 1 also shows the calculation results of the surface layer uneven distribution ratio (Mo2 / Mo1) of the MoO3 content (Mo2) to the MoO3 content (Mo1).
[0194] From the results of the surface layer uneven distribution ratio (Mo2 / Mo1), the molybdenum content in the surface layer of the forsterite particles determined by XPS surface analysis was higher than the molybdenum content determined by XRF analysis in the forsterite particles of Examples 1, 4, and 8. This confirmed that molybdenum is unevenly distributed in the surface layer of the forsterite particles, and it is expected that various functions due to molybdenum will be effectively exerted.
[0195] The forsterite particles obtained in Examples 2 and 5, in which MoO3 was used as the raw material, had a higher MoO3 content (Mo1) than the other Examples, even though the raw material (Mg compound + Si compound) / Mo compound ratio was 10 / 1. Also, in Examples 6 to 9, in which MoO3 was used in combination with the raw material, the MoO3 content (Mo1) tended to be higher.
[0196] In this way, by controlling the amount and type of the molybdenum compound used, the amount of molybdenum contained in the forsterite particles could be controlled, and forsterite particles containing the desired amount of molybdenum could be produced.
[0197] Referring to Table 2, there was a tendency that larger sized forsterite particles were obtained as the molar ratio (Mo / (Mg+Si)) of molybdenum atoms to magnesium and silicon atoms in the raw material increased.
[0198] In this way, by controlling the amount of the molybdenum compound used, the particle size of the forsterite particles could be controlled, and forsterite particles having a desired particle size could be produced.
[0199] The configurations and combinations thereof in each embodiment are merely examples, and additions, omissions, substitutions, and other modifications of the configurations are possible without departing from the spirit of the present invention. Furthermore, the present invention is not limited to each embodiment, but is limited only by the scope of the claims.
Claims
1. Forsterite particles containing molybdenum, Mg based on 100% by mass of the forsterite particles 2 SiO 4 Contains 65% by mass or more, The molybdenum content in the forsterite grains is determined by XRF analysis of the forsterite grains, and is a content (Mo 1 ) calculated as MoO 3 relative to 100 mass% of the forsterite grains, which is 0.05 to 35 mass%, the molybdenum content in the surface layer of the forsterite particle is 0.05 to 25 mass% in terms of MoO 3 content (Mo 2 ) relative to 100 mass% of the surface layer of the forsterite particle, as determined by XPS surface analysis of the forsterite particle; Forsterite grains, in which a surface layer uneven distribution ratio of molybdenum (Mo 2 / Mo 1 ) is 1.1 or more.
2. 2. The forsterite particles according to claim 1, wherein the average particle size of the primary particles of the forsterite particles is 0.1 to 100 μm.
3. The specific surface area measured by the BET method is 0.02 to 20 m 2 The forsterite particles according to claim 1, wherein the Mn content is 1 / g.
4. The method for producing forsterite particles according to any one of claims 1 to 3, comprising calcining a magnesium compound, and silicon or a silicon compound in the presence of a molybdenum compound.
5. 5. The method for producing forsterite particles according to claim 4, wherein the molybdenum compound is at least one compound selected from the group consisting of molybdenum trioxide, lithium molybdate, potassium molybdate and sodium molybdate.
6. The method for producing forsterite particles according to claim 4, wherein the sintering temperature is 800 to 1600°C.
7. 5. The method for producing forsterite particles according to claim 4, wherein a molar ratio (Mo / (Mg+Si)) of molybdenum atoms to magnesium and silicon atoms in the raw material to be fired is 0.001 to 5.
Citation Information
Patent Citations
Industrial producing method of high-purity magnesium olivine crystal material
CN101037207A
Method and material for lithium ion battery anodes
CN106463702A
Method for producing forsterite fine particles
JP2016222517A
Olivine-type lithium-based oxide primary particle for mixed positive electrode active material and method for producing the same
JP2020043009A
Silane-treated forsterite microparticles and method for producing the same, organic solvent dispersion of silane-treated forsterite microparticles, and method for producing the same
JP2020100561A